Green Synthesis of Hydroxyapatite from Oyster Shell Waste for Catalytic Applications - Adibah Rahmat; Yahaya, Izat; Hana Fareeha Azizuddin; Hanis Imran Hisham; Muhammad Azizi Najmi Mamat Ali; Nodiana Mohamad; Nur Aqilah Abdullah; Nur Nadirah Muhammad Sukri; Vyranath Ko Mon; Riana Rayner (Enhanced Knowledge in Sciences and Technology, 2025)
The synthesis of hydroxyapatite from oyster shells was successfully accomplished using a calcination process to transform calcium carbonate (CaCO₃) into calcium oxide (CaO), followed by hydrothermal treatment. Characterization techniques, including Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDX), X-ray Diffraction (XRD), and Fourier Transform Infrared Spectroscopy (FTIR), confirmed the formation of hydroxyapatite. SEM images revealed a granular, clustered morphology, while EDX analysis indicated the presence of calcium, phosphorus, and oxygen, consistent with hydroxyapatite’s expected composition. XRD patterns displayed characteristic hydroxyapatite peaks, and FTIR spectra confirmed the presence of phosphate groups. The synthesized hydroxyapatite demonstrated high catalytic efficacy in removing Cr(III) from an aqueous Cr(NO₃)₃ solution, achieving an 82.12% removal efficiency, reducing the concentration from 850 ppm to 152 ppm within 3 hours. These results highlight hydroxyapatite’s potential in environmental remediation applications. Further optimization of synthesis conditions, alongside studies on catalyst regeneration and scalability, is recommended to enhance material performance and practical applicability.